Pengaruh Intensitas dan Adiksi Penggunaan Media Sosial terhadap Perilaku Phubbing di Provinsi DKI Jakarta - Gouwtama, Yunita (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2024)
The use of technology, especially social media users, has an impact on human behavior patterns, especially in big cities such as DKI Jakarta Province. One of the impacts of using social media is the emergence of phubbing behavior. This research aims to determine the influence of intensity and addiction of social media use on phubbing behavior in DKI Jakarta Province. The method used is a survey method with a probability sampling technique with a total of 400 respondents taken within the period 31 October – 12 November 2022. The result is in line with Media Dependency Theory, if someone depends on media that can fulfill their needs, so that media becomes important for the user. The results of the hypothesis test state that the intensity of social media use has a positive, significant, and low effect of 11.4% on phubbing behavior. Addiction to using social media has a positive, significant, and strong effect of 45.1% on phubbing behavior. These figures show that the intensity and addiction of social media use significantly influence phubbing behavior.